Compressive and shear strength performance of jute fibre-reinforced concrete under long-term environmental conditions - Uwemedimo Nyong Wilson; Adamu Yusuf; John Engbonye Sani; Samson Olalekan Odeyemi; Okereke Chika Eze; Adewumi J. Babafemi; Kelvin O. Yoro (Journal of Infrastructure Preservation and Resilience)
Abstract In an attempt to build affordable structures using locally-sourced materials without alkali-based pre-treatment, it is equally important to ascertain that these materials are sustainable. This research investigates the long-term sustainability of jute fibre-reinforced concrete by evaluating its compressive and shear strength. Different fibre volume fractions (0%, 0.25%, 0.5%, and 0.75%) were tested in concrete grades ranging from 25–40 MPa. A total of 48 cube samples and 16 beam samples were cured for 28 days and then exposed to harsh conditions for 12 months. The cubes were tested for compressive strength, while the beams were subjected to a three-point shear test. Results indicated that concrete with 0.5% jute fibre had the highest compressive strength after 12 months, with an increase of up to 11.61% for various concrete grades compared to control specimens. The maximum shear strength was observed in samples containing 0.75% jute fibre, with strength increments ranging from 9.39% to 23.76% for different grades. However, the density of the jute fibre-reinforced concrete decreased by an average of 2.53%, and the workability was also reduced. Overall, the study concludes that jute fibre can enhance both compressive and shear strength over long-term exposure, demonstrating its potential as a sustainable reinforcement material for concrete without significant strength loss. The longterm effect of alkali-treated jute fibre on compressive and shear strength of concrete can be considered for further studies.